If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(3x + 4) + 2(5x + -3) = 0 Reorder the terms: 3(4 + 3x) + 2(5x + -3) = 0 (4 * 3 + 3x * 3) + 2(5x + -3) = 0 (12 + 9x) + 2(5x + -3) = 0 Reorder the terms: 12 + 9x + 2(-3 + 5x) = 0 12 + 9x + (-3 * 2 + 5x * 2) = 0 12 + 9x + (-6 + 10x) = 0 Reorder the terms: 12 + -6 + 9x + 10x = 0 Combine like terms: 12 + -6 = 6 6 + 9x + 10x = 0 Combine like terms: 9x + 10x = 19x 6 + 19x = 0 Solving 6 + 19x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + 19x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 19x = 0 + -6 19x = 0 + -6 Combine like terms: 0 + -6 = -6 19x = -6 Divide each side by '19'. x = -0.3157894737 Simplifying x = -0.3157894737
| 6+2(z-3)=5z+3 | | 12-3x=x-4(2+2x) | | 9(3x+2)+4(x-4)=33 | | 5c-1=39 | | 4(x-1)-x= | | 4(x-1)+x= | | 5(2n+4)=7(9n+2)+1 | | 8h+4=28 | | 3x+2-5x-7=4x+2 | | 4(2n+2)=8(6n+8)+2 | | 5k-9=16 | | X+0.7=0.35 | | x^4/3-x^2/3-8=0 | | 32=2pix | | 5(3b-4)=16-3b | | 4x+y^2+x^4+25=360 | | 2(3n+1)=6+(7n+4)+5 | | 8(x-3)=7x-13 | | 22x=2x | | 10j=160 | | 12*x=2 | | 3x-8=64-9x | | 3 = b5– 1 | | 3/13x-1/5=-2 | | MC+3x(3)=36 | | x/9=201 | | 6x+6=4x+20 | | yxy/yxyxyxyxyxyxyxyxy | | 3(x-4)=2(x-7) | | 8x-3=7x+4 | | 4z/7-6=-3 | | 0.05(y-5)+0.10y=0.05y-0.20 |